2008
DOI: 10.1007/s10856-008-3625-9
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of hydrogels based on poly(2-hydroxyethyl methacrylate) with extracellular matrix proteins

Abstract: Infrared attenuated total reflection spectroscopy was used for in situ observation of the deposition of collagen I on poly(2-hydroxyethyl methacrylate-co-methacrylic acid, 2.9%) hydrogels and subsequent attachment of laminin or fibronectin on the collagen surface. While there was no adsorption of collagen dissolved in an acid solution on the hydrogel surface, it deposited on the surface at pH 6.5. The collagen layers with attached laminin or fibronectin were stable on hydrogel surface in physiological solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Cell growth increased after collagen I coating of hydrogel surface. However, cell growth significantly increased by the attachment of fibronectin and laminin on the collagen layer, especially with fibronectin attachment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell growth increased after collagen I coating of hydrogel surface. However, cell growth significantly increased by the attachment of fibronectin and laminin on the collagen layer, especially with fibronectin attachment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since this hydrophilic polymer shows a poor interface with cells, blending with other polymers provided improved biocompatibility. 24,25 In general, pHEMA-based materials can be produced in hydrogel form with different shapes, for example, membrane, film, microparticle, disk, and tubes. Recently, we synthesized different types of pHEMA-based SPHs.…”
Section: Scaffold Synthesis and Characterizationmentioning
confidence: 99%
“…Although EWC has been used as a criterion for grading the capacity for cell adhesion in hydrogels, this parameter in the case of PHEMA appears to be related to the polarity of the surface 55 rather than to its wettability, 58 and therefore may not epitomize the global effect of hydration-related factors. Among the various reported strategies aimed at promoting or enhancing cell attachment to PHEMA surfaces, we can mention copolymerization, 55,[59][60][61] acid etching, 62,63 chemical grafting, 64,65 inclusion of ECM components, [66][67][68] fabrication of topographic features on the surface, 69 ablation of the surface with high-energy laser radiation, 70 or electropolymerization. 71 In a recent study, 72 on the surface of PHEMA we created a topography that replicated features present on the surface of lotus leaves (Nelumbo nucifera), a well-known natural superhydrophobic surface, 73,74 and we found that the lotus-like topography induced not only greater hydrophobicity of the substratum but also an enhancement of the in vitro attachment and growth of human corneal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although EWC has been used as a criterion for grading the capacity for cell adhesion in hydrogels, this parameter in the case of PHEMA appears to be related to the polarity of the surface 55 rather than to its wettability, 58 and therefore may not epitomize the global effect of hydration-related factors. Among the various reported strategies aimed at promoting or enhancing cell attachment to PHEMA surfaces, we can mention copolymerization, 55,5961 acid etching, 62,63 chemical grafting, 64,65 inclusion of ECM components, 6668 fabrication of topographic features on the surface, 69 ablation of the surface with high-energy laser radiation, 70 or electropolymerization. 71…”
Section: Introductionmentioning
confidence: 99%